A case of relapsing isolated neurosarcoidosis in an 18-year-old male patient successfully treated by corticosteroids - Kalmárová, Klaudia; Kurča, Egon; Sivák, Štefan; Michalik, Jozef; Plank, Lukáš; Vyšehradský, Róbert; Zeleňák, Kamil; Šutovský, Juraj; Nosáľ, Vladimir (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2019)
Sarcoidosis is a granulomatous multisystemic disease of unknown cause most often affecting the lungs, lymph nodes of the pulmonary hilus, eyes, skin, and other structures including central (CNS) or peripheral nervous system (PNS). Isolated neurosarcoidosis is extremely rare. The diagnosis of isolated neurosarcoidosis is challenging because of its rarity, variety of manifestations, and the lack of systemic signs. We report relapsing and remitting isolated intracranial neurosarcoidosis in an 18-year-old male patient who undervent complex diagnostics including cerebral and meninges biopsy. Patient was succesfully treated with corticosteroids.